Patient vs provider reports of aberrant medication-taking behavior among opioid-treated patients with chronic pain who report misusing opioid medication. Issue 8 (August 2016) - Nikulina, Valentina; Guarino, Honoria; Acosta, Michelle C.; Marsch, Lisa A.; Syckes, Cassandra; Moore, Sarah K.; Portenoy, Russell K.; Cruciani, Ricardo A.; Turk, Dennis C.; Rosenblum, Andrew
Abstract : Abstract: During long-term opioid therapy for chronic noncancer pain, monitoring medication adherence of patients with a history of aberrant opioid medication-taking behaviors (AMTB) is an essential practice. There is limited research, however, into the concordance among existing monitoring tools of self-report, physician report, and biofluid screening. This study examined associations among patient and provider assessments of AMTB and urine drug screening using data from a randomized trial of a cognitive–behavioral intervention designed to improve medication adherence and pain-related outcomes among 110 opioid-treated patients with chronic pain who screened positive for AMTB and were enrolled in a pain program. Providers completed the Aberrant Behavior Checklist (ABC) and patients completed the Current Opioid Misuse Measure (COMM) and the Chemical Coping Inventory (CCI). In multivariate analyses, ABC scores were compared with COMM and CCI scores, while controlling for demographics and established risk factors for AMTB, such as pain severity. Based on clinical cutoffs, 84% of patients reported clinically significant levels of AMTB and providers rated 36% of patients at elevated levels. Provider reports of AMTB were not correlated with COMM or CCI scores. However, the ABC ratings of experienced providers (nurse practitioners/attending physicians) were higher than those of less experienced providers (fellows) and were correlated with CCI scores and risk factors for AMTB. Associations between patient- and provider-reported AMTB and urine drug screening results were low and largely nonsignificant. In conclusion, concordance between patient and provider reports of AMTB among patients with chronic pain prescribed opioid medication varied by provider level of training. Abstract : There is poor concordance between patient and provider reports of aberrant opioid medication-taking behaviors among patients with chronic pain. Concordance varies by provider's level of expertise.